Negotiating work and household demands: Effects of conflict management strategies in Dutch households on the labor supply of male and female employees - Philip Wotschack; Rafael Wittek (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2006)
This paper explains variation in the labor supply of male and female employees by taking into account differences in conflict management strategies in Dutch households. While existing accounts on labor supply either emphasize household restrictions, firm influences or institutional constraints the approach taken here focuses on strategies of spouses to handle time-based interpersonal workhousehold conflicts. Using a sample of 304 male and 238 female cohabiting employees drawn from 30 Dutch organizations, we analyze how gender moderates the effect of conflict management strategies on labor supply, measured as the amount of actual working hours. Building on role congruity theory, we distinguish between two types of conflict management behavior. 'Agentic' strategies are characterized by a low concern for other, and are usually ascribed to a male gender role. 'Communal' strategies are characterized by a high concern for other and are usually ascribed to a female gender role. OLS and multilevel regression analysis supports two hypotheses. First, working women relying on communal strategies to resolve time-allocation conflicts with their male partners will be more successful in achieving their objective to work more hours than women who don't use communal strategies. Second, labor supply of working men increases with their use of agentic strategies. The findings support the proposition from role congruity theory that (in-)congruence between the (male) provider role and a female gender role explains gender differences in the impact of interpersonal conflict management behavior on labor supply. – – Der Artikel untersucht den Einfluss von Konfliktstrategien im Haushalt auf das Erwerbsarbeitszeitvolumen männlicher und weiblicher Beschäftigter. Während in der bisherigen Forschung Unterschiede im Arbeitsangebot durch Haushaltsrestriktionen, betriebliche Faktoren und institutionelle Merkmale erklärt werden, akzentuiert der vorliegende Beitrag unterschiedliche Strategien von Paaren zur Bewältigung interpersonaler Zeitallokationskonflikte. Anhand einer Stichprobe von 304 männlichen und 238 weiblichen Beschäftigten aus 30 niederländischen Betrieben wird untersucht, auf welche Weise geschlechtsspezifische Unterschiede den Einfluss der Konfliktstrategien auf das Erwerbsarbeitszeitvolumen moderieren. Ausgehend von der 'role congruity theory' werden zwei Typen von Konfliktstrategien unterschieden: 'agentic strategies' und 'communal strategies'. Die Ergebnisse der OLS-Regressionsanalyse und Mehrebenenanalyse bestätigen die folgenden Hypothesen: Der unterschiedliche Einfluss von Konfliktstrategien auf das Erwerbsarbeitszeitvolumen von männlichen und weiblichen Beschäftigten lässt sich aus der (In-)Kongruenz von Versorgerrolle und geschlechtsspezifischen Rollenattributen erklären. Weibliche Beschäftigte können ein größeres Erwerbsarbeitszeitvolumen realisieren, wenn sie zur Lösung von Zeitallokationskonflikten im Haushalt 'communal strategies' anwenden. Das Erwerbsarbeitszeitvolumen männlicher Beschäftigter steigt, wenn sie zur Lösung von Zeitallokationskonflikten im Haushalt 'agentic strategies' anwenden.
Keywords: 300; Familienökonomik; Konflikt; Männer; Frauen; Arbeitsangebot; Hausarbeit; Schätzung; Niederlande